Aspek Psikologi Buku Ajar Bahasa Arab Madrasah Ibtidaiyyah Kelas VI (Studi Analisis Deskriptif) - Ersa Antika Rahmandha; Dian Risky Amalia; Abdelwahab Ayman (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Teaching materials are a critical component in the curriculum that supports the learning process. This study analyzes the psychological aspects of the Arabic textbook for Grade VI, aiming to evaluate the effectiveness of the textbook in meeting the students' needs. The research method employed is descriptive qualitative with a literature study approach. The data sources consist of primary and secondary data relevant to the topic. The primary data in this study is the Arabic Textbook based on KMA Number 189 of 2019. Secondary data serves as a complement to provide additional information from the primary data and is obtained from several literatures such as academic journals and papers. The results of the study show that: (1) The textbook encourages students to learn independently through clear instructions and exercises that are relevant to daily life; (2) The textbook provides activities that stimulate students' creativity, such as thematic dialogues and tasks that require self-expression; (3) The textbook instills positive values such as discipline, responsibility, and care through practical learning materials; (4) The textbook helps students reflect on their learning process and organize learning strategies through language analysis and reflective exercises. Therefore, the Grade VI Arabic textbook is suitable for use, although there are several weaknesses that need to be addressed to enhance learning effectiveness.